2005
DOI: 10.1080/10284150500047161
|View full text |Cite
|
Sign up to set email alerts
|

Reducing mitochondrial decay with mitochondrial nutrients to delay and treat cognitive dysfunction, Alzheimer's disease, and Parkinson's disease

Abstract: Mitochondrial decay due to oxidative damage is a contributor to brain aging and age-related neurodegenerative diseases, such as Alzheimer's disease (AD) and Parkinson's disease (PD). One type of mitochondrial decay is oxidative modification of key mitochondrial enzymes. Enzyme dysfunction, that is due to poor binding of substrates and coenzymes may be ameliorated by supplementing adequate levels of substrates or coenzyme precursors. Such supplementation with mitochondrial nutrients (mt-nutrients) may be useful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
117
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 127 publications
(119 citation statements)
references
References 236 publications
(253 reference statements)
2
117
0
Order By: Relevance
“…Thus, oxidative damage, destruction of calcium homeostasis and mitochondrial dysfunction are essentially consequences of Glu-induced excitotoxicity. Consistent with these findings, antioxidants and mitochondrial nutrients [8,9] may be promising candidates for the prevention and treatment of these diseases.…”
Section: Introductionsupporting
confidence: 63%
“…Thus, oxidative damage, destruction of calcium homeostasis and mitochondrial dysfunction are essentially consequences of Glu-induced excitotoxicity. Consistent with these findings, antioxidants and mitochondrial nutrients [8,9] may be promising candidates for the prevention and treatment of these diseases.…”
Section: Introductionsupporting
confidence: 63%
“…The complementary effect of LA and ALC on cognitive and mitochondrial dysfunction has been shown in ageing rats [27,28,40]. One reason is that LA+ALC act on different pathways necessary for mitochondria: LA is a mitochondrial antioxidant and cofactor of pyruvate dehydrogenase, while ALC is an energy enhancer [25,41]. Another possibility is that ALC, although stimulating mitochondrial function, may cause side effects of oxidative stress in mitochondria [42], while LA, an effective mitochondrial antioxidant, is able to ameliorate that side effect of ALC.…”
Section: Discussionmentioning
confidence: 99%
“…We assigned these compounds to different groups of mitochondrial nutrients as previously described. 16 Previous studies in rodents have shown that combinations of nutrients have synergistic effects in various metabolic pathways and are more potent than treating the animals with individual nutrients. 48 For example, supplementing mice with lipoic acid, carnitine, and CoQ10 had a more significant beneficial effect on agerelated oxidative stress than individual treatment with these compounds.…”
Section: Nutrient Formulas Effectively Rescued Mitochondrial Dysfunctmentioning
confidence: 99%
“…As described in previous publications, 13,15,16 we have identified a group of mitochondria targeting antioxidants and cofactors, which are referred to as ''mitochondrial nutrients.'' With these mitochondrial nutrients, we aim to reverse the mitochondrial dysfunction that occurs during the aging process.…”
Section: Introduction Dmentioning
confidence: 99%